Urban segregation and environmental sustainability: challenges and perspectives for Montes Claros – MG - Moura, Rafael Soares Duarte de (2024)
Urbanization is a dynamic and complex process that involves multiple interactions between infrastructure development, population growth, and the transformation of spaces into urban areas. This article aims to analyze the environmental implications arising from the culture of segregationist urbanization, with a specific focus on the Master Plan of the municipality of Montes Claros, located in the state of Minas Gerais, Brazil. The primary objective of this study is to explore the environmental issues associated with segregationist urbanization, using Montes Claros as a case study. To achieve this, a methodology based on a literature review was employed, allowing for a critical analysis of relevant literature on the topic, alongside documentary research that involved a detailed examination of the Montes Claros Master Plan. The article first addresses the historical process of population and urban growth in the city, highlighting how urbanization has developed in a segregationist manner over time. This type of urbanization has led to a series of environmental challenges, reflected in unequal access to urban infrastructure and the degradation of natural resources. The analysis of the Montes Claros Master Plan reveals that, although it contains guidelines aimed at promoting more equitable and sustainable urban development, the effective implementation of these policies faces significant obstacles. The study argues that the Master Plan, when consistently applied and properly monitored, can serve as a crucial tool for urban planning and management, capable of fostering a more inclusive, equitable, and environmentally just urbanization process. Finally, the article concludes that for Montes Claros to achieve more harmonious and sustainable urban development, it is imperative that there is a continuous effort in urban planning and infrastructure investment, with an emphasis on environmental preservation and improving the quality of life for the population. This requires public policies that not only recognize but also actively address existing inequalities, promoting an urban space that is truly inclusive and sustainable.